(untitled) (Tribhuvan University Law Journal, 2025)
The topic of same-sex marriage has sparked a lot of discussion around the world, and Nepal is no exception. In recent years, Nepali society has become more accepting of the LGBTIQA++ community, challenging old social stigmas. The Constitution of Nepal, introduced in 2072 BS (2015 AD), provides legal protections for sexual minorities, creating a positive environment for the potential acceptance of same-sex marriages in the future. The courts have also played a key role in protecting the rights of sexual minorities, including granting legal protections like the right to marry, in line with the constitution’s principles. However, despite the progress in Nepal’s legal system, same-sex marriage is still a complicated issue both in practice and in law, mainly because there are no specific laws addressing it. This article looks at the current status of same-sex marriage recognition in Nepal, considering the country’s constitutional and legal frameworks, which may either support or challenge these rights. It focuses on important laws, like the Constitution of Nepal, the National Civil Code, and the Citizenship Act, which play a role in same-sex unions. The article also explores the challenges posed by the lack of legal recognition of same-sex marriages, as there are no laws explicitly covering this issue. The article raises important questions about whether the current constitutional laws are enough to make same-sex marriage legally clear and enforceable in Nepal, or if more legal reforms are needed to ensure equal rights and protections for same-sex couples.